2020
DOI: 10.1080/09640568.2020.1816532
|View full text |Cite
|
Sign up to set email alerts
|

Renewable and nonrenewable energy consumption, trade and CO2 emissions in high emitter countries: does the income level matter?

Abstract: This study analyzes the effects of increased income and renewable energy on environmental quality, which has been ignored in the existing literature. An important contribution of this study is to analyze the role of renewable and nonrenewable energy in relation to the rising level of carbon emissions in the leading emitting countries. This research further examines the heterogeneous impacts of rising income levels and EKC investigation for CO 2 emissions. The Kao cointegration, generalized method of moments (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(45 citation statements)
references
References 82 publications
3
36
0
Order By: Relevance
“…To avoid limiting the ability of the study to forecast the future accurately and consistently the study employed the heterogeneous panel estimation techniques to test for cross-sectional dependence. The CIPS panel unit root test developed by Pesaran (2007) can verify the homogeneity, unit root properties and cross sectional independence (Cui et al 2019a, b;Fatima et al 2020).…”
Section: Preliminary Analysismentioning
confidence: 99%
“…To avoid limiting the ability of the study to forecast the future accurately and consistently the study employed the heterogeneous panel estimation techniques to test for cross-sectional dependence. The CIPS panel unit root test developed by Pesaran (2007) can verify the homogeneity, unit root properties and cross sectional independence (Cui et al 2019a, b;Fatima et al 2020).…”
Section: Preliminary Analysismentioning
confidence: 99%
“…Khan et al ( 2020b ) highlighted renewable energy, regulatory pressure, and environmentally friendly policies in South Asian countries. Meanwhile, Fatima et al ( 2021 ) observed the effects of higher income and renewable energy on environmental quality and found that increasing the use of renewable energy reduces CO 2 emissions in high-emitting countries. However, in the GCC countries, the link between diversification and renewable energy is not well understood.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The duty cycle is fed by the pulse width modulation (PWM) comparator to generate pulses for switching a MOSFET or IGBT OFF and ON [29]. Equation (2) shows that the output voltage is larger than the input voltage whenever the duty cycle step size is regulated from 0.2 to 0.9 [30]. Figure 5a shows a simplified network of the boost converter.…”
Section: Boost Converter Design and Controlmentioning
confidence: 99%
“…The demand for renewable energy as an alternative source of conventional power generation is increasing because of a decrease in its production expenses, zero carbon emissions, and economical tariffs [1]. Renewable energy production is predicted to increase by 6.7% by 2030 [2]. The report of the Joint Research Center revealed that the global installation of PV plants was 315 GW in 2016, with a cumulative increase of 40% annual production over the last 15 years.…”
Section: Introductionmentioning
confidence: 99%